ANALISIS DETERMINAN YANG MEMPENGARUHI PEMBIAYAAN MURABAHAH PADA BANK UMUM SYARIAH DI INDONESIA - Putri Dwiawani; Heri Sudarsono (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
This study aims to analyze the determinants of murabahah financing as seen from microeconomic factors such as Third Party Funds, Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return On Assets (ROA), Financing to Deposit Ratio (FDR), and BOPO as well as from macroeconomic factors such as BI rate and Inflation that are seen as having an effect in the short and long term. Analysis in this study uses secondary time series data taken from monthly data of OJK and BPS, namely from January 2015 to July 2020. Observation used as many as 67 observations and analysis methods used is Auto-Regressive Distributed Lag (ARDL) with Eviews 9 application. The results obtained from this study are in the short term variables that do not affect Murabahah Financing in Sharia Commercial Banks including CAR, ROA, NPF, BOPO, and Inflation. Meanwhile, Third Party Funds and FDR have a positive relationship and have a significant influence on Murabahah Financing. Then, the BI Rate affects Murabahah Financing but the relationship is negative. In the long term, the variable that has a positive and significant influence on Murabahah Financing is CAR. On the other hand, the NPF and BI Rate have a negative and significant effect on Murabahah Financing. While the rest, DPK, ROA, FDR, BOPO, and Inflation had no effect Murabahah Financing in Sharia Commercial Banks significantly in the long term.